'Non-zoonotic' pasteurella multocida infection in an immunocompromised patient - Beenish Fayyaz (Greater Baltimore Medical Center, 2018)
Discovered by Louis Pasteur in 1880, Pasteurella multocida is the most common cause of zoonotic infection in humans which is transmitted via pet bites and/or scratches. However, animal contact may be absent or not identified in up to 40% of cases which usually occur in individuals with comorbidities. Despite having a low virulence, PM can cause serious and life threatening infections in rare instances. In such cases, prompt diagnosis and appropriate treatment can lead to miraculous recovery.